Preliminary Identification of Bioactive Compounds from Commelina nudiflora. L and its Antioxidant, Antibacterial Activities - Kuppusamy, Palaniselvam; M. M., Yusoff; Mohammed, Suliman; Gaanty Pragas, Maniam; Natanamurugaraj, Govindan (2013)
The methanolic extract of weed plant Commelina nudiflora was evaluated for preliminary phytochemical analysis and its antioxidant, antibacterial activity. The antibacterial activity was determined in the extracts using the agar disc diffusion method. The different concentration (50, 75, 100 μg/ml) of methanolic extract of Commelina nudiflora was tested against human pathogenic microorganisms. The zone of inhibition of extracts was compared standards as streptomycin for antibacterial activity. The results showed that the significant inhibition of the bacterial growth was shown against E.coli and Salmonella typhi with 11 mm and 9 mm respectively. The phytochemical analyses of the plant extract were carried out by using standard phytochemical methods. Also the free radical scavenging activity of C. nudiflora methanolic extract was subjected into DPPH and ABTS assay. In conclusion the microbial and free radical scavenging activity of the Commelina nudiflora was due to the presence of various secondary metabolites such as saponin, alkaloids, polyphenols and flavonoids. C.nudiflora plant contains a novel bioactive compounds that may serve as control many endemic diseases.